Exchange rate hysteresis in UK imports from the South Asian countries - Nusrate Aziz; Ahmad Hassan Ahmad (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2018)
We investigate and find evidence for the hysteresis hypothesis in UK imports from South Asian countries, using a monthly sample data that covers 1999 to 2012. This paper finds evidence of the asymmetric effect of exchange rate volatility that "large" depreciations significantly reduce UK imports from Bangladesh; however, "large" appreciations do not increase the imports significantly. We also find a partial support for the hysteresis hypothesis in UK import from India, Pakistan and Sri Lanka. We find that hysteresis can be both country- and commodity-dependent, which is largely consistent with previous empirical studies. Theoretical literature suggests that hysteresis occurs due to the presence of sunk costs, however, we find that hysteresis occurs even beyond the sunk costs.
Keywords: C22; F31; F32; 330; Hysteresis hypothesis; sunk costs; exchange rate; bilateral trade